E-commerce and Consumer Protection Address Challenges in the Beauty Products Sector - Tiara Yogi Dwi Amelia; Rina Arum Prastyanti (International Forum of Researchers and Lecturers, 2025)
The rapid development of information technology has significantly driven the growth of e-commerce as one of the main channels in modern commercial activities. In the beauty product sector, digital platforms offer consumers easier access and simultaneously expand market reach for business actors. However, this advancement also brings various challenges, particularly in relation to consumer protection. Common issues include product authenticity, information transparency, transaction security, and dispute resolution mechanisms. In this context, legal protection for consumers has become an urgent matter that cannot be overlooked. This study aims to analyze the forms of legal protection available to consumers of beauty products in e-commerce transactions and to assess the effectiveness of existing regulations in addressing these challenges. Using a normative juridical approach, the study evaluates relevant legislation, such as Law Number 8 of 1999 concerning Consumer Protection, along with other regulations related to electronic transactions. The findings reveal that although legal instruments have been established to safeguard consumer rights, their implementation still encounters obstacles, including limited supervision of online business actors and low consumer literacy regarding their rights. Therefore, efforts are needed to strengthen regulations, improve consumer education, and optimize the roles of supervisory and dispute resolution institutions. In this way, the consumer protection system in the e-commerce sector—particularly for beauty products—can operate more effectively and provide a greater sense of security for the public in conducting digital transactions.